The Effect of Entrepreneurship Education on Social Entrepreneurship Intentions, Moderation of Entrepreneurial Inclination, Mediation of Entrepreneurial Attitudes in Islamic Boarding School Students in Cirebon City - Syafitri, Syafitri; Kurjono, Kurjono; Khaled, Amgad S. D. (Islamic Research, 2024)
The purpose of this paper is to examine students' entrepreneurial intentions in students at Cirebon Islamic boarding schools and to analyze family background groups. The Grand Theory used is Ajzen's Theory of Planned Behavior. There are 250 Islamic boarding school students throughout Cirebon. Data was collected by means of a questionnaire containing statements on a five-point numerical type scale. Data analysis using Regression. The results identified that entrepreneurship education is the main predictor of social entrepreneurial intention. Entrepreneurial attitudes are proven to mediate the effect of entrepreneurship education on social entrepreneurship intentions. This study found no differences in family background. The limitation of this research lies in the number of samples and students of Islamic boarding schools in the city of Cirebon which have not been widespread. Further research is suggested to predict social entrepreneurship intentions in students with other variables besides entrepreneurship education, entrepreneurial attitudes and entrepreneurial tendencies.